Peroperacní detekce plicních lézí pri mininvazivní operativĕ - Hromádka, P; Cernohorský, S; Skach, J; Baader, M; Gaalová, R; Sercl, M (Rozhledy v chirurgii, 2010)
Currently, peroperative palpatory examination of the lungs represents standard method, however the development of the new mini-invasive surgery techniques devoid of palpable facilities, demands utilization of different procedures. The authors present their experiences involving detection of pulmonary lesions during thoracoscopic surgery visually, by endoscopic instruments, preoperative dye marking and peroperative ultrasonography via an endoscopic ultrasonic probe (all performed in Liberec District Hospital a.s.). The article describes operation techniques and tactics of thoracoscopic surgeries performed with pulmonary pathological processes in both subpleural and pulmonary parenchyma locations.
Keywords: torakoskopie; Minimally Invasive Surgical Procedures; Lung Diseases; Humans; miniinvazivní chirurgické výkony; Palpation; palpace; Thoracoscopy; lidé; plicní nemoci